Advances in Austrian economics. Vol. 3 - Prychitko, Peter J.; Boettke, David L. (Emerald, 1996)
This third volume in the series is divided into four parts. The first presents a symposium on models of socialism, the second presents current research, the third, review essays, and the fourth, book reviews.
Keywords: Austrian school of economics.; elektronické knihy; electronic books